2017
DOI: 10.1016/j.ydbio.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring p53 by MDM2 and MDMX is required for endocrine pancreas development and function in a spatio-temporal manner

Abstract: Although p53 is not essential for normal embryonic development, it plays a pivotal role in many biological and pathological processes, including cell fate determination-dependent and independent events and diseases. The expression and activity of p53 largely depend on its two biological inhibitors, MDM2 and MDMX, which have been shown to form a complex in order to tightly control p53 to an undetectable level during early stages of embryonic development. However, more delicate studies using conditional gene-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…The primers used for qPCR were 5’-ACCATTGTGGACACACCAGG-3’ and 5’-GAACCTGTGACCACCTGCTA-3’ for human ARTS and 5’-CAGGGCAGGGCTACCACTAG-3’ and 5’-TGATGCAGGGCCTTCATGA-3’ for mouse ARTS. The primers for human and mouse p21 were previously described 30 , 31 .…”
Section: Methodsmentioning
confidence: 99%
“…The primers used for qPCR were 5’-ACCATTGTGGACACACCAGG-3’ and 5’-GAACCTGTGACCACCTGCTA-3’ for human ARTS and 5’-CAGGGCAGGGCTACCACTAG-3’ and 5’-TGATGCAGGGCCTTCATGA-3’ for mouse ARTS. The primers for human and mouse p21 were previously described 30 , 31 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, disruption of p53 function is closely associated with several key BP leading to diabetes, including loss of pancreatic beta cells, interference with glucose homeostasis at the body level, and IR in peripheral tissues. Studies have shown that oxidative stress and elevated levels of free fatty acids lead to activation of p53, which leads to pancreatic beta cell death (20)(21)(22)(23)(24)(25). Meanwhile, p53 can affect peripheral glucose metabolism by directly regulating glucose uptake, glycolysis and gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MDM2 and MDMX can also cooperatively and independently suppress p53 s transcriptional activity by binding to the N-terminal transcriptional domain of p53 via their own N-termini [52]. The mutual dependence of MDM2 and MDMX for their p53-inactivating functions, as well as their essential roles in controlling p53 level and activity in vivo, has been demonstrated in several mouse genetic studies [53][54][55][56][57][58]. Therefore, because both MDM2 and MDMX are p53 responsive transcriptional targets, they play essential roles in controlling p53 level and activity in a negative feedback fashion during embryogenesis and organogenesis.…”
Section: The Mdm2-mdmx-p53 Loopmentioning
confidence: 97%